ENHANCEMENT QUALITY OF HOTS ASSESSMENT OF PRE-SERVICE TEACHERS THROUGH PROJECT-BASED LEARNING - Mukarramah Kori Mukarramah (PEDAGOGIA, 2023)
To fulfill the professionalism of pre-service teachers in the aspect of pedagogic competence, each pre-service teacher will be equipped with knowledge related to the preparation of test instruments including cognitive test instruments based on high-order thinking skills (HOTS) which can be mastered only if students gain real experience regarding the preparation of these instruments through project-based learning. The purpose of this study is to describe the learning process and what projects are produced and describe the level of success. The method used is classroom action research proposed by Kemmis which goes through the stages of planning, action, observation, and reflection. The results of this study are, first; project-based learning that students go through can achieve the expected abilities, namely, students can develop valid and reliable test instruments as well as other supporting documents that support the success of the HOTS-based test instruments that are compiled. Second; Project-based learning has experienced success as indicated by the results of the learning questionnaire and the recapitulation of increased learning outcomes before and after the implementation of project-based learning on the HOTS questions.